2020
DOI: 10.3390/microorganisms8020234
|View full text |Cite
|
Sign up to set email alerts
|

Predominance of Distinct Listeria Innocua and Listeria Monocytogenes in Recurrent Contamination Events at Dairy Processing Facilities

Abstract: The genus Listeria now comprises up to now 21 recognized species and six subspecies, with L. monocytogenes and L. innocua as the most prevalent sensu stricto associated species. Reports focusing on the challenges in Listeria detection and confirmation are available, especially from food-associated environmental samples. L. innocua is more prevalent in the food processing environment (FPE) than L. monocytogenes and has been shown to have a growth advantage in selective enrichment and agar media. Until now, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 61 publications
1
21
0
2
Order By: Relevance
“…Since the occurrence of L. monocytogenes contamination was similar for both categories (Table 2), we confirmed that heat treatment of milk had little impact on the presence of L. monocytogenes in the smears and that, in the majority of our observations, cheese is more likely to become contaminated after coagulation [18,35,49].…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Since the occurrence of L. monocytogenes contamination was similar for both categories (Table 2), we confirmed that heat treatment of milk had little impact on the presence of L. monocytogenes in the smears and that, in the majority of our observations, cheese is more likely to become contaminated after coagulation [18,35,49].…”
Section: Resultssupporting
confidence: 65%
“…by ISO enrichment methods, PCR-based species differentiation should be performed on typical Listeria colonies isolated on selective agar [ 32 , 33 ]. Persistence of L. innocua was shown to occur more frequently than persistence of L. monocytogenes and is, therefore, seen as an indicator of inadequate hygiene [ 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most internationally recognized scheme was proposed by Ragon et al (2008), an adaptation of the initially proposed scheme by Salcedo et al (2003). This typing method is still currently used (Kaszoni-Rückerl et al, 2020;Stessl et al, 2021).…”
Section: Listeria Monocytogenes Genotypes Prevalence In the Environmentmentioning
confidence: 99%
“…In recent times, investigators have reported different numbers of species for the genus; hence, it is important to clarify the number of species available now. A recent article [1] reported that the genus Listeria comprises up to 21 species. The authors relied on the information in the List of Prokaryotic Names with Standing in Nomenclature at the ‘Bacterio.net’ website (http://www.bacterio.net/listeria.html) to conclude 21 species.…”
Section: Full-textmentioning
confidence: 99%